1987
DOI: 10.3146/i0095-3679-14-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of No-tillage, Minimum, and Full Tillage Cultural Practices on Peanuts

Abstract: The no-tillage system for peanuts (Arachis hypogaea L.) was investigated &om 1978 to 1981 in comparison with minimum and full tillage. Dficulty in controlling weeds, soil compaction, and reduced yields were problems associated with no-tillage peanut culture. No-tillage plots yielded 600 to 2400 kgha less than full tillage each year, while the minimum tillage plots were intermediate in yield. Peanut grades were not different except in 1980 when the no-tillage system graded less than full or minimum tillage. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 4 publications
1
42
0
3
Order By: Relevance
“…Root rots caused by several soilborne fungi, including Fusarium spp., Phytophthora spp., and Rhizoctonia spp., were generally lower under conservational tillage systems (15). Although Garren (4) demonstrated that plant residue increased the incidence of stem rot caused by Sclerotium rolfsii Sacc., recent studies have shown that the presence of residue associated with minimum tillage had little to no effect on the incidence of stem rot (3,5,7). In a five-year study (7) in Alabama, stem rot .severity in peanut did not increase under reduced tillage systems even though plant residues remained on top ofthe soil,.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Root rots caused by several soilborne fungi, including Fusarium spp., Phytophthora spp., and Rhizoctonia spp., were generally lower under conservational tillage systems (15). Although Garren (4) demonstrated that plant residue increased the incidence of stem rot caused by Sclerotium rolfsii Sacc., recent studies have shown that the presence of residue associated with minimum tillage had little to no effect on the incidence of stem rot (3,5,7). In a five-year study (7) in Alabama, stem rot .severity in peanut did not increase under reduced tillage systems even though plant residues remained on top ofthe soil,.…”
mentioning
confidence: 99%
“…In other systems, seed are planted into a seedbed prepared in a narrow band of soil that had been ' Interest in the use of conservational tillage in peanut production has developed during the past decade; but the use of such a production system in peanut is usually associated with several unfavorable factors. These include a suspected increase in disease development related to residue buildup, poor plant stands due to poor seedbed preparation, reduced plant growth due to compacted soil, lack ofsatisfactory weed control, and reduced pod and seed quality (3,5,16,17,18). Diseases caused by both soilborne and' foliar pathogens decrease in a number of crops grown using conservational tillage systems that do not eliminate residue from the soil surface (2,10,14,15).…”
mentioning
confidence: 99%
“…The increase in weed pressure in NT systems was expected, particularly given the inability to incorporate pre-emergence herbicides. Grichar and Boswell (1987) also observed an increase in weed pressure in NT peanut production. However, it is important to note that post-emergence herbicide applications can be used to successfully control any remaining weeds, as they were in this study.…”
Section: Volunteer Peanut and Weed Populationsmentioning
confidence: 80%
“…In North Carolina, reduced tillage decreased sclerotinia blight where considerable residue was left for ground cover prior to planting (Jordan et al, 2003). Grichar and Boswell (1987) observed that no-till systems decreased peanut yield 600 to 2400 kg ha 21 in Texas and cited a lack of weed control and compaction as the reasons for reduced yield. The varied results suggest more research is needed to identify the soils and environments under which reduced or NT systems perform well, including measuring the impact of plant diseases.…”
mentioning
confidence: 99%
“…In summary, five studies have given conservation tillage a clear advantage in either yield, improved quality, or net economic returns (Brandenburg et al 1998;Hartzog and Adams, 1989;Hurt et al, 2006;Marois and Wright, 2003;Tubbs and Gallaher, 2005). Seven studies, four of which were conducted with the virginia market type, favored conventional, high intensity tillage practices that could not be considered conservation tillage Grichar and Boswell, 1987;Jordan et al, 2001;Jordan et al, 2003;Minton et al, 1991;Wright and Porter, 1991a;Wright and Porter, 1995). Not surprisingly, seven other studies showed no differences in conservation tillage systems versus conventional tillage (Chapin et al, 2001;Grichar, 2006;Grichar and Smith, 1992;Grichar and Smith, 1992;Johnson et al, 2001;Wiatrak et al, 2004).…”
mentioning
confidence: 99%